Polypoidal Choroidal Vasculopathy: http://doi.org/10.36351/pjo.v37i2.972 - Nadeem, Sana (Pakistan Journal of Ophthalmology, 2021)
A 76-year-old, hypertensive lady, presented with a three year history of gradual decrease in vision in her right eye. Examination revealed a large, bullous, serous pigment epithelial detachment (PED) of right fovea, a choroidal neovascular membrane, clusters of hard exudates, drusen and surrounding, multifocal, small PEDs. The left eye showed a series of small PEDs mostly on the inferior macula, pigmentary disturbance of the retinal pigment epithelium and scant hard exudates. A diagnosis of Polypoidal choroidal vasculopathy was made. We decided to treat her with intravitreal Bevacizumab injections in her right eye. At 18 months of follow up, her PEDs had resolved and visual acuity had improved from 6/60 OD to 6/36. Key Words: Polypoidal Choroidal Vasculopathy, Age Related Macular Degeneration, Pigment Epithelial Detachment, Choroidal Neovascular Membrane.